Identification of broad base and stable sources of resistance to Fusarium wilt in pigeonpea - VISHWA DHAR*, SHASHI MISHRA (Indian Phytopathology, 2010)
Vascular wilt of pigeonpea caused by Fusarium udum Butler is one of the most widely distributed and damaging diseases. Because of its soil borne nature and long survival, growing resistant varieties is the best option for managing the disease. However, instability of resistance observed in some newly developed resistant varieties due to pathogenic variability in F.udum has necessiated to identify donors for breeding of varieties with broad base, multiple variant resistance. Twenty one elite genotypes of pigeonpea recommended as wilt resistant donors were evaluated against three variants ( Vr 2, Vr 4 and Vr 5) of F.udum identified at Indian Institute of Pulses Research, Kanpur, under artificial inoculations. This has enabled to identify three genotypes viz. ICP 8860, ICP 8863 and ICP 14722 as uniformly resistant to all the three variants revealing their high and broad based resistance to Fusarium wilt. Three other genotypes viz. KPBR 80-2-1, PI 397430 and DPPA 85-14 showing oderate resistance against all the three variants also hold good promise. All the six genotypes can be effectively utilized as donors for breeding stable wilt resistant varieties. Genotypes found resistant to one or two of these variants may have limited applications in wilt resistance breeding programme.